Metode Six Sigma untuk Menurunkan Produk Cacat Hasil Muat (Studi kasus PT. XY) - Karimah, Akhlakul; W, Taswati Nova (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
XY is a building materials industry company, which often faces the challenge of high levels of defective products due to loading processes. To solve this problem, the study applied the Six Sigma method to minimize the occurrence of defects in the loading process. (Define, Measure, Analyze, Improve, Control). The first step defines the characteristics of the resulting defect. The second step measures the creation of a control diagram. The third step analyzes the main factors of the occurrence of product defects. The fourth step improves is a proposal for improvement to reduce the failure. The final control process is making recommendations for improvement, this is entirely carried out by the company. From the results of the research, it was found that the defective product was loaded at a rate of 1,107 with a probability of damage of 7,204,102 products per million chances. (DPMO). Based on the Pareto diagram of the level of damage caused by the production process, damaged by the forklift, damages during handling, and damages by the pallet. Based on the fishbone diagram, improvements are needed on human factors, environmental factors, material factors, mechanical factors, and method factors. Keywords: DMAIC, Fishbone Diagram, Pareto Diagram, Six Sigma